Exploring The Potential of Geographical Information Technology (GIT) in Archaeology - Azizul, Ahmad; Mohd Zulhafiz, Said; Nor Khairunnisa, Talib; Yaniza Shaira, Zakaria; Nur Afiqah, Ariffin; Ailis Elizabeth, Epa; Tarmiji, Masron; Lindah Roziani, Jamru (2024)
For years, archaeologists have relied on traditional maps and spatial analysis to visually understand the distribution of artefacts and features across archaeological sites. This paper examines the potential of geospatial approaches for archaeology by assessing the advantages and challenges of using Aerial Photography (AP), Remote Sensing (RS), Geographic Information System (GIS), and Global Positioning System (GPS) in archaeological research. Hence, we conducted a literature review to substantiate our discussion. The introduction of Geographical Information Technology (GIT) has provided archaeologists with sophisticated tools to analyse and visualise the distribution and archaeological data innovatively. As such, geospatial analysis has gained important recognition as one of the tools to help archaeologists. By integrating AP, RS, GIS, and GPS into their research, archaeologists can now analyse large quantities of data while understanding spatial roles. This has allowed them to gain new insights into the distribution and pattern of these archaeological features.